Quantitative analyses of products and rates in polyethylene depolymerization and upcycling - Yu-Hsuan Lee; Jiakai Sun; Susannah L. Scott; Mahdi M. Abu-Omar (STAR Protocols, 2023)
Summary: Depolymerization and upcycling are promising approaches to managing plastic waste. However, quantitative measurements of reaction rates and analyses of complex product mixtures arising from depolymerization of polyolefins constitute significant challenges in this emerging field. Here, we detail techniques for recovery and analysis of products arising from batch depolymerization of polyethylene. We also describe quantitative analyses of reaction rates and products selectivity. This protocol can be extended to depolymerization of other plastics and characterization of other product mixtures including long-chain olefins.For complete details on the use and execution of this protocol, please refer to Sun et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.